Computational Thinking in Language Arts When Teaching Creative and Expository Writing - Bayraktar, Aysegul; Gulbahar, Yasemin (CTE-STEM 2022 conference, 2022)
In language arts instruction, computational thinking skills can be implemented through language arts activities, especially in teaching of diamante poems and expository writing. Instructional materials and activities for an elective language arts course lasting 14 weeks for two hours per week were prepared by the researcher. During the course, an invited speaker presented one instructional session for 23 pre-service elementary school teachers regarding the '˜Scratch Program' used to create digital stories. The following week another expert instructed computational thinking skills to these pre-service teachers about how to implement these skills into their language arts activities. Additionally, the researcher provided three hours and 30 minutes of instruction regarding poetry writing and 10 hours instruction on expository writing to increase the pre-service teachers' abstraction, separation, pattern recognition, logical reasoning, pattern decomposition, error detection, and algorithm design skills. Furthermore, the pre-service teachers were trained regarding various writing genres including creative writing. The pre-service teachers were later asked to submit a portfolio of their writing samples and the activities prepared specifically for developing elementary school students' computational thinking skills along with their reflective journals written regarding their experience of learning computational thinking skills. The pre-service teachers were not having or realizing any computational thinking skills in the beginning of the semester. Whereas when the semester ended, their reflective journals and written samples from portfolios showed they had become knowledgeable about computational thinking skills as well as strategies and/or activities used to increase their future students' computational thinking skills.